Drought Risk Assessment and Zoning in the Tarim River Basin, Xinjiang, China - Xiangzhi Kong; Qiao Li; Hongfei Tao; Mahemujiang Aihemaiti (Agriculture)
The Tarim River Basin is an important grain and cotton base in Xinjiang, China. Indeed, cotton production in this basin accounts for one-third of the total cotton production in China. The Tarim River Basin is characterized also by the presence of forestry activities and fruit plantations. However, frequent long-term droughts have seriously affected local agricultural productivity. In this paper, a new standardized precipitation evapotranspiration index (nSPEI), with an improved drought detection effect, was constructed based on the standardized precipitation index (SPI) and the standardized precipitation evapotranspiration index (SPEI). This drought index was subsequently employed as a hazard indicator of disaster-causing factors in the Tarim River Basin. In addition, a drought disaster risk assessment model was constructed using the natural disaster system theory. This model was applied to analyze the hazard of drought-disaster-causing factors, the exposure of disaster-affected bodies, the vulnerability of disaster-bearing environments, drought prevention/mitigation capabilities, and comprehensive drought disaster risks in the Tarim River Basin over the 2001–2021 period. The results demonstrated the applicability of the 12-month nSPEI (nSPEI-12) in the Tarim River Basin. Specifically, the nSPEI-12 values exhibited a decreasing trend, highlighting an aridification trend in the basin. In addition, a 25% increase in the vegetation cover of the Tarim River Basin was observed from 2000 to 2023 and remained unchanged at 4.5%. On the other hand, a decreasing trend of the vegetation cover was found in the remaining parts of the basin. The hazard level of the disaster-causing factors and the exposure of bearing bodies were high in the northeastern and northwestern parts of the Tarim River Basin, respectively. The disaster prevention/mitigation capacity was greater in the northern and southwestern parts, while the vulnerability level of disaster-bearing environments decreased from the northwestern part to the southeastern part. The western and northern parts of the Tarim River Basin exhibited the highest drought risk levels, followed by the northeastern and southeastern parts.